2017
DOI: 10.1080/08927936.2017.1310987
|View full text |Cite
|
Sign up to set email alerts
|

Food for Thought: Assessing Visitor Comfort and Attitudes toward Carcass Feeding at the ABQ BioPark Zoo

Abstract: Food for Thought: Assessing Visitor Comfort and Attitudes toward Carcass Feeding at the ABQ BioPark Zoo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…Free-range enclosures, which promote natural or species-specific behavior in zoo animals, have also been shown to improve visitor perceptions of the welfare of zoo animals, visitor experience and increase visitor viewing times (Bryan et al, 2017;Mun et al, 2013;Price et al, 1994;Wilson et al, 2003). Additionally, enclosures that have enrichment items for zoo animals have been found to increase visitor ratings of the enclosures, to be associated with positive perceptions of zoo animals and their welfare, to increase positive attitudes towards enrichment items, and to increase viewing times and interactions with zoo animals at exhibits by visitors (Davey et al, 2005;Davey, 2007a;Kutska, 2009;Roth et al, 2017;Tripp, 1985;Wood, 1998). For example, Roth et al (2017) found that visitor attitudes towards carcass feeding were positive, which also increased positive attitudes towards animal welfare and behavior.…”
Section: Visitor Attitudes and Perceptionsmentioning
confidence: 97%
See 1 more Smart Citation
“…Free-range enclosures, which promote natural or species-specific behavior in zoo animals, have also been shown to improve visitor perceptions of the welfare of zoo animals, visitor experience and increase visitor viewing times (Bryan et al, 2017;Mun et al, 2013;Price et al, 1994;Wilson et al, 2003). Additionally, enclosures that have enrichment items for zoo animals have been found to increase visitor ratings of the enclosures, to be associated with positive perceptions of zoo animals and their welfare, to increase positive attitudes towards enrichment items, and to increase viewing times and interactions with zoo animals at exhibits by visitors (Davey et al, 2005;Davey, 2007a;Kutska, 2009;Roth et al, 2017;Tripp, 1985;Wood, 1998). For example, Roth et al (2017) found that visitor attitudes towards carcass feeding were positive, which also increased positive attitudes towards animal welfare and behavior.…”
Section: Visitor Attitudes and Perceptionsmentioning
confidence: 97%
“…Additionally, enclosures that have enrichment items for zoo animals have been found to increase visitor ratings of the enclosures, to be associated with positive perceptions of zoo animals and their welfare, to increase positive attitudes towards enrichment items, and to increase viewing times and interactions with zoo animals at exhibits by visitors (Davey et al, 2005;Davey, 2007a;Kutska, 2009;Roth et al, 2017;Tripp, 1985;Wood, 1998). For example, Roth et al (2017) found that visitor attitudes towards carcass feeding were positive, which also increased positive attitudes towards animal welfare and behavior. However, there is variation within the literature on the effect of different types of enrichments (e.g., naturalistic vs. unnaturalistic) on visitor perceptions and attitudes where some have argued there can be substantial variation in visitor responses to enrichment, in particular to where it is provided (e.g., on exhibit or off exhibit; Cottle et al, 2010;Ings et al, 1997;McPhee et al, 1998), whereas others have found no effect of enrichment type on visitor perceptions (Kutska, 2009).…”
Section: Visitor Attitudes and Perceptionsmentioning
confidence: 99%
“…Many studies found that behaviours which visitors perceived to be active and natural were considered positive indicators of welfare [10,16,19,35,38,41,43,46,52,54,59,62,70,77,88,[94][95][96][97][98][99][100][101][102][103][104][105]. In contrast, behaviours perceived as abnormal or inactive were thought to be negative indicators [2,16,19,38,40,41,47,61,64,71,73,95,99,104,[106][107][108].…”
Section: Animal Behaviourmentioning
confidence: 99%
“…Free-range enclosures, which promote natural or species-specific behavior in zoo animals, have also been shown to improve visitor perceptions of the welfare of zoo animals, visitor experience and increase visitor viewing times (Bryan et al, 2017;Mun et al, 2013;Price et al, 1994;Wilson et al, 2003). Additionally, enclosures that have enrichment items for zoo animals have been found to increase visitor ratings of the enclosures, to be associated with positive perceptions of zoo animals and their welfare, to increase positive attitudes towards enrichment items, and to increase viewing times and interactions with zoo animals at exhibits by visitors (Davey et al, 2005;Davey, 2007;Kutska, 2009;Roth et al, 2017;Tripp, 1985;Wood, 1998). For example, Roth et al (2017) found that visitor attitudes towards carcass feeding were positive which also increased positive attitudes towards animal welfare and behavior as a result of this feeding enrichment.…”
Section: Visitor Attitudes and Perceptionsmentioning
confidence: 99%
“…Additionally, enclosures that have enrichment items for zoo animals have been found to increase visitor ratings of the enclosures, to be associated with positive perceptions of zoo animals and their welfare, to increase positive attitudes towards enrichment items, and to increase viewing times and interactions with zoo animals at exhibits by visitors (Davey et al, 2005;Davey, 2007;Kutska, 2009;Roth et al, 2017;Tripp, 1985;Wood, 1998). For example, Roth et al (2017) found that visitor attitudes towards carcass feeding were positive which also increased positive attitudes towards animal welfare and behavior as a result of this feeding enrichment. However, there is variation within the literature on the effect of different types of enrichments (e.g.…”
Section: Visitor Attitudes and Perceptionsmentioning
confidence: 99%